High blood pressure and sedentary behavior in adolescents are associated even after controlling for confounding factors - Christofaro, Diego Giulliano Destro [UNESP]; Andrade, Selma Maffei de; Cardoso, Jefferson Rosa; Mesas, Arthur Eumann; Codogno, Jamile Sanches [UNESP]; Fernandes, Rômulo Araújo [UNESP] (Taylor & Francis Online, 2015)
The aim of this study was to determine whether high blood pressure (HBP) is associated with sedentary behavior in young people even after controlling for potential confounders (gender, age, socioeconomic level, tobacco, alcohol, obesity and physical activity). In this epidemiological study, 1231 adolescents were evaluated. Blood pressure was measured with an oscillometric device and waist circumference with an inextensible tape. Sedentary behavior (watching television, computer use and playing video games) and physical activity were assessed by a questionnaire. We used mean and standard deviation to describe the statistical analysis, and the association between HBP and sedentary behavior was assessed by the chi-squared test. Binary logistic regression was used to observe the magnitude of association and cluster analyses (sedentary behavior and abdominal obesity; sedentary behavior and physical inactivity). HBP was associated with sedentary behaviors [odds ratio (OR) = 2.21, 95% confidence interval (CI) = 1.41-3.96], even after controlling for various confounders (OR = 1.68, CI = 1.03-2.75). In cluster analysis the combination of sedentary behavior and elevated abdominal obesity contributed significantly to an increased likelihood of having HBP (OR = 13.51, CI 7.21-23.97). Sedentary behavior was associated with HBP, and excess fat in the abdominal region contributed to the modulation of this association.
Keywords: Abdominal obesity; Adolescents; High blood pressure; Physical activity; Sedentary behaviors